A Comparative Study of Chinese and American Marital Conflicts Under Cooperative Principle: ——Taking Desperate Housewives and Marriage Battle as Examples (Asian Journal of Social Science Studies, 2022)
As an important theory in pragmatics, Cooperative Principle has been used in the process of in-depth researches on various language phenomena, such as euphemism, irony, humor, vagueness and so on, whereas similar research on conflict discourse has not received extensive attention yet. Among all the conflict discourse, marital conflict is daily but exceptionally complicated. What makes it even more complicated is that marital conflicts under different cultural contexts have distinctive features. Under Cooperative Principle, this paper focuses on two TV series, Desperate Housewives, an American drama, and Marriage Battle, a domestic drama, and analyzes the construction patterns of Chinese and American marital conflict talk from the perspective of comparative study.